Redefining Healthcare and Workforce Engagement: A Comprehensive Examination of AI, Skill Development, and Incentives in Banking, Healthcare, and Fraud Prevention in the Petroleum Industry - Alexandra Harry; Ali Khan (JURIHUM : Jurnal Inovasi dan Humaniora, 2024)
This thorough investigation explores how cutting-edge technologies like artificial intelligence (AI) and cloud computing are revolutionizing a number of industries, with particular attention to supply chain risk management, employee performance, cloud security, healthcare innovations, and database optimization. Emphasizing the link between ongoing learning and better organizational outcomes, the need of training and development is emphasized, especially in improving employee performance within the banking industry in Noakhali. Block chain technology and AI's involvement in predictive analytics in healthcare provide patient-centered care and safe data management while posing crucial privacy and ethical questions. Cloud Security Posture Management (CSPM), which emphasizes automated risk detection and ongoing monitoring to protect sensitive data, becomes a crucial approach for businesses using cloud environments. AI-driven query optimization in relational databases is also discussed, demonstrating how this technology may automate processes and improve performance and resource efficiency. Additionally, supply chain management predictive analytics driven by AI gives businesses the insight they need to anticipate possible disruptions, enhancing stakeholder collaboration and resilience. The combination of these observations emphasizes how important it is for businesses to embrace strategic approaches to technology integration in order to improve operational effectiveness and promote long-term success. Businesses can position themselves for success in a competitive context by utilizing these innovations to build a framework that is safe, effective, and flexible enough to handle the challenges of a changing environment.